Non‐HIV‐infected patients with Pneumocystis pneumonia in the intensive care unit: A bicentric, retrospective study focused on predictive factors of in‐hospital mortality. (10th January 2022) - Wang, Yuqiong; Huang, Xu; Sun, Ting; Fan, Guohui; Zhan, Qingyuan; Weng, Li
Abstract: Background: The incidence of Pneumocystis pneumonia (PCP) among patients without human immunodeficiency virus (HIV) infection continues to increase. Here, we identified potential risk factors for in‐hospital mortality among HIV‐negative patients with PCP admitted to the intensive care unit (ICU). Methods: We retrospectively analyzed medical records of 154 non‐HIV‐infected PCP patients admitted to the ICU at Peking Union Medical College Hospital (PUMCH) and China‐Japan Friendship Hospital (CJFH) from October 2012 to July 2020. Clinical characteristics were examined, and factors related to in‐hospital mortality were analyzed. Results: A total of 154 patients were enrolled in our study. Overall, the in‐hospital mortality rate was 65.6%. The univariate analysis indicated that nonsurvivors were older (58 vs. 52 years, P = 0.021), were more likely to use high‐dose steroids (≥1 mg/kg/day prednisone equivalent, 39.62% vs. 55.34%, P = 0.047), receive caspofungin during hospitalization (44.6% vs. 28.3%, P = 0.049), require invasive ventilation (83.2% vs. 47.2%, P < 0.001), develop shock during hospitalization (61.4% vs. 20.8%, P < 0.001), and develop pneumomediastinum (21.8% vs. 47.2%, P = 0.001) and had higher Acute Physiology and Chronic Health Evaluation (APACHE) II scores on ICU admission (20.32 vs. 17.39, P = 0.003), lower lymphocyte counts (430 vs. 570 cells/μl, P = 0.014), and lower PaO2/FiO2 values (mmHg) on admission (108 vs. 147, P = 0.001). Multivariate analysis showed that age (odds ratio [OR] 1.03; 95% confidence interval [CI] 1.00–1.06; P = 0.024), use of high‐dose steroids (≥1 mg/kg/day prednisone equivalent) during hospitalization (OR 2.29; 95% CI 1.07–4.90; P = 0.034), and a low oxygenation index on admission (OR 0.99; 95% CI 0.99–1.00; P = 0.014) were associated with in‐hospital mortality. Conclusions: The mortality rate of non‐HIV‐infected patients with PCP was high, and predictive factors of a poor prognosis were advanced age, use of high‐dose steroids (≥1 mg/kg/day prednisone equivalent) during hospitalization, and a low oxygenation index on admission. The use of caspofungin during hospitalization might have no contribution to the prognosis of non‐HIV‐infected patients with PCP in the ICU.